Autofocus-Based Estimation of Penetration Depth and Permittivity of Ice Volumes and Snow Using Single SAR Images - Benedikter, Andreas; Rodríguez-Cassolà, Marc; Betancourt-Payan, Felipe; Krieger, Gerhard; Moreira, Alberto (IEEE Transactions on Geoscience and Remote Sensing, 2021)
An intrinsic challenge in the geophysical interpretation of low-frequency SAR imagery of semi-transparent media, such as ice sheets, is the position ambiguity of the scattering structures within the glacial volume. Commonly tackled by applying interferometric and tomographic techniques, their spaceborne implementation exhibits by orders higher complexity compared to missions relying on single SAR images, making them cost expensive or, in the context of planetary missions, even impossible due to limited navigation capability. Besides, even these sophisticated techniques are commonly biased due to inaccurate permittivity estimates, leading to geometric distortions up to several meters. We present a novel inversion procedure to estimate volume parameters of ice sheets, namely, the depth of the scattering layer within the glacial volume and the dielectric permittivity of the ice, based on single-image single-polarization SAR acquisitions. The information is inherent in the processed SAR data as phase errors on the azimuth signals resulting from uncompensated non-linear propagation of the radar echoes through ice. We suggest a local map-drift autofocus approach to quantify and spatially resolve the phase errors and an inversion model to relate them to the penetration depth and permittivity. Testing the proposed technique using P-band SAR data acquired by DLR’s airborne sensor F-SAR during the ARCTIC15 campaign in Greenland shows promising results and good agreement with tomographic products of the analyzed test site.
Keywords: Ice; Permittivity; Synthetic aperture radar; Radar; Spaceborne radar; Scattering; Radar imaging; synthetic aperture radar (SAR); autofocus; tomography; cryosphere; glacier; penetration; depth

Non-destructive testing of arbitrarily shaped refractive objects with millimetre-wave synthetic aperture radar imaging - Ullmann, Ingrid; Adametz, Julian; Oppelt, Daniel; Benedikter, Andreas; Vossiek, Martin (Journal of Sensors and Sensor Systems, 2018)
Millimetre-wave (mmW) imaging is an emerging technique for non-destructive testing. Since many polymers are transparent in this frequency range, mmW imaging is an attractive means in the testing of polymer devices, and images of relatively high resolution are possible. This contribution presents an algorithm for the precise imaging of arbitrarily shaped dielectric objects. The reconstruction algorithm is capable of automatically detecting the object's contour, followed by a material-sensitive reconstruction of the object's interior. As an example we examined a polyethylene device with simulated material defects, which could be depicted precisel
lhft_intern.bib::Ullmann18b

Periodic orbits for interferometric and tomographic radar imaging of Saturn’s Moon Enceladus - Benedikter, Andreas; Wickhusen, Kai; Hussmann, Hauke; Stark, Alexander; Damme, Friedrich; Rodríguez-Cassolà, Marc; Krieger, Gerhard (Acta Astronautica, 2021)
Spaceborne synthetic aperture radar interferometry and tomography are well-established techniques for the exploration of terrestrial ice sheets. In the frame of DLR’s mission concept Enceladus Explorer (EnEx), these techniques are considered for providing topography, deformation, and composition measurements, as well as 3-D metric-resolution imaging of the Enceladean ice crust. However, the formation of repeat-pass interferometric and tomographic acquisitions requires spacecraft orbits with almost perfectly repeating ground tracks and sufficient inclination for providing access to the most-interesting south polar region with its plumes. Unfortunately, the low Enceladus mass and its proximity to Saturn commonly lead to extreme instabilities for orbit inclinations beyond 60°. We show that existing orbit solutions close to this inclination barrier resulting from searches in simplified dynamic models do not exhibit sufficient stability in realistic n-body ephemeris simulations for providing the necessary repeat characteristic. We present a grid-search strategy in an ephemeris model for identifying highly-stable, periodic orbits satisfying the repeating ground track requirement. The resulting orbit solutions are assessed regarding their stability, repeat characteristic, and robustness to uncertainties in the gravitational model, navigation inaccuracies, and drag by the ejected gas and dust of the plumes. Global simulations of interferometric and tomographic acquisition geometries are used to assess the suitability of the orbits. The identified orbits provide sufficient inclination and long-term stability to sustain the required repeat characteristic up to few hundreds of days with repeat-pass baselines in the order of hundreds of meters. This may allow a consistent implementation of radar interferometric and tomographic imaging modes for a future Enceladus mission. Besides, the high stability may offer favorable conditions for other remote sensing modalities.
Keywords: Enceladus; orbit; orbit design; radar; SAR interferometry; SAR tomography

Potential of a Multimodal Orbital Radar Mission for the Exploration of Enceladus - Benedikter, Andreas; Rodriguez-Cassola, Marc; Krieger, Gerhard; Scheiber, Rolf; Martin del Campo Becerra, Gustavo; Horn, Ralf; Stelzig, Michael; Moreira, Alberto; Vossiek, Martin (EGU General Assembly 2020, 2020)
An Enceladus mission launched within a realistic time frame (e.g., launch between 2025 and 2040 and a transfer time of about ten years) would likely arrive as the sun is departing or gone from the most interesting South Polar Region marked by its active jets erupting through the ice crust. This almost drives the need for a radar instrument enabling the imaging, mapping and characterization of the moon independent of sunlight illumination. The known ice penetration capability of radar waves in the tens of MHz up to few GHz range allows for the exploration of subsurface features, whereas the surface may be imaged with high level of detail in higher frequencies up to several tens of GHz. In the frame of the Enceladus Explorer Initiative (EnEx) of the German Aerospace Center (DLR), we are currently investigating the potential of a multimodal orbital radar instrument to be used as a companion to a lander mission and to contribute in the understanding of the structure, composition and temporal variation of the Enceladean ice crust and the involved geophysical processes. The considered orbit geometries, strongly constrained by the presence of Saturn, allow for global coverage and offer half-daily revisit of the South Polar Region. We suggest a multi frequency system working concurrently in high frequency (e.g., Ka-band) and lower frequency (e.g., P-band) for surface and subsurface exploration, respectively, both capable of operating in a variety of modes: i) high resolution imaging used as a synthetic aperture radar (SAR), ii) SAR interferometer for topography, permittivity and surface and volume deformation estimates, iii) nadir looking configuration operating as an altimeter for elevation estimates and as a sounder for subsurface exploration with great penetration capability, iv) radiometer for surface temperature estimates and inversion of temperature profiles, and v) bistatic measurements between the radar instrument and an ice penetrating probe deployed by the lander with similarities to the CONSERT instrument of ESA's Rosetta mission. In this presentation, we evaluate the potential of the different modes concerning their scientific output and their usefulness for supporting the success of a lander mission. In particular the performance of SAR imaging and interferometry (single- and repeat-pass) modes are analysed, which are expected to provide key information for landing site selection such as structure, composition and topography of the surface and subsurface with metric resolution. For validation, we present results of a SAR campaign conducted using DLR's airborne sensor F-SAR over an alpine glacier, with simultaneous X- and L-band acquisitions. The campaign incorporates repeat- and single-pass acquisitions, as well as circular flights, which provide interferometric and tomographic measurements with observation geometries similar to those of an Enceladus mission. Furthermore, we provide an analysis towards a bistatic sounding experiment. Utilizing the transmission line between the radar instrument and a transponder integrated in an ice penetrating probe allows for the inversion of the spatial distribution of the dielectric ice properties and associated geophysical parameters (e.g., density, grain size, temperature, and salinity).

Radar Interferometry and Tomography for the Exploration of Enceladus' Surface and Subsurface: Feasibility and Potential - Benedikter, Andreas; Wickhusen, Kai; Hussmann, Hauke; Stark, Alexander; Rodriguez-Cassola, Marc; Krieger, Gerhard; Damme, Friedrich (AGU Fall Meeting, 2021)

Radar Travel Time Tomography for Subsurface Ice Exploration at Saturn's Moon Enceladus - Huber, Christian; Benedikter, Andreas; Krieger, Gerhard; Rodriguez-Cassola, Marc (2021 18TH EUROPEAN RADAR CONFERENCE (EURAD), 2022)
We present an iterative travel time inversion approach for mapping the subsurface permittivity distribution within the ice crust of Saturn's moon Enceladus utilizing bistatic transmission lines between an orbital radar and an active target (transponder) located in the ice. The approach builds on the dependence between the measured radar travel times and the underlying permittivity distribution. The estimated permittivity distribution can then be used to infer physical parameters of the Enceladus ice crust such as density, temperature, and grain size. Building on the same rationale, we furthermore suggest an effective localization strategy for targets located in the ice crust. Both permittivity distribution estimate and localization show promising results when tested on synthetic dat
CRIS-Team WoS Importer:2022-08-26

Subsurface TomoSAR imaging of the Mittelbergferner glacier in the Austrian Alps - Martin del Campo Becerra, Gustavo; Benedikter, Andreas; Amao-Oliva, Joel; Scheiber, Rolf (EUSAR 2021; 13th European Conference on Synthetic Aperture Radar, 2021)

Taking a Look Beneath the Surface: Multicopter UAV-Based Ground-Penetrating Imaging Radars - Grathwohl, Alexander; Stelzig, Michael; Kanz, Julian; Fenske, Patrick; Benedikter, Andreas; Knill, Christina; Ullmann, Ingrid; Hajnsek, Irena; Moreira, Alberto; Krieger, Gerhard; Vossiek, Martin; Waldschmidt, Christian (IEEE Microwave Magazine, 2022)
The field of multicopter unmanned aerial vehicles (UAVs) has seen massive technological advances and decreasing costs over the last decade. Due to the higher prevalence and availability of these multicopter UAVs, there have also been rapid improvements in the software interfaceability, enabling the easy integration of custom software for flight planning and controllers. This opened up completely new possibilities, such as low-cost individual aerial photography, the most common civilian application. Furthermore, lightweight multicopters became widely accessible to the public, boosting the development of UAVs even more.<br

Towards the Validation of a Volumetric Imaging Concept for the SAR Exploration of Enceladus - Benedikter, Andreas; Rodriguez-Cassola, Marc; Krieger, Gerhard; Scheiber, Rolf; Martin del Campo Becerra, Gustavo; Horn, Ralf; Moreira, Alberto; Stelzig, Michael; Vossiek, Martin (AGU Fall Meeting 2019, 2019)

Virtual Synthetic Aperture Radar Target Based on a Miniaturized Monostatic Digital Delay Transponder - Stelzig, Michael; Benedikter, Andreas; Horn, Ralf; Jaeger, Marc; Keller, Martin; Scheiber, Rolf; Krieger, Gerhard; Vossiek, Martin (IEEE Microwave and Wireless Components Letters, 2021)
The ice penetrating capability of low-frequency radar systems may offer a unique potential for the detection, localization, and guidance of exploratory ice-penetrating probes for cryospheric applications. As these probes exhibit a comparably small radar cross section (RCS), reliable detection, especially in high clutter surroundings, such as ice sheets, is prevented. As a solution, a miniaturized monostatic digital delay transponder is developed and tested regarding its functionality with an airborne synthetic aperture radar (SAR) sensor.
Keywords: Transponders; Radar; Syntethic aperture radar (SAR); Radar cross-sections (RCS); Delays; Probes; Ice; Pulse compression